The program relevance of future engineer creativity development on the basis of scientific research - Valentina G. Ryndak; Gulmira S. Saifutdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper contains answers to questions that show that the formation of creativity is vital for the future of the engineer, engineering education. At the same time, the authors explore how the creativity of future engineers should be formed in the process of studying at a technical university, and propose strategies to make creativity a part of every engineering curriculum and course. The paper presents the relevance of the program for the formation of the future engineers creativity based on the theoretical analysis of the world experience of domestic and foreign scientists. The possibilities and methods of its implementation in the process of scientific research are shown. The presented research is based on the theory of knowledge, the activity approach, the pedagogy of creativity and the methodology of scientific research. The best practices of foreign scientists in solving the problem of forming the creativity of future engineers are presented. The purpose of the study is to justify the need to create a program aimed at developing the creativity of future engineers.